A case of dyskeratosis congenita with portal hypertension associated with jugular venous anomaly - Yusuf YAZGAN; Levent DEMİRTÜRK and Melih ÖZEL and Çınar BAŞEKİM (Turkish Journal of Gastroenterology, 2019)
-